2009
DOI: 10.1063/1.3224962
|View full text |Cite
|
Sign up to set email alerts
|

Influence of powerful laser irradiation on electromagneto-optical dependences of yttrium iron garnets

Abstract: Electromagneto-optical properties of yttrium iron garnets have been investigated in a longitudinal geometry by using optical polarimetry method. It is revealed that irradiation of yttrium iron garnet films by powerful laser impulse leads to essential increase in the electromagneto-optical effect value, which can be due to the elimination of the local mechanical strain or nonuniform pressure in them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Occurrence of linear on the electric field component of EMO signal in some points of a film (Figure 2), in our opinion, has a following explanation. In our earlier studies, only square-law on the electric field EMOE was observed in separate areas of YIG and bismuth-substituted YIG films (without additional external influence on the sample) [8][9][10]. The MEE and EMOE that are linearly dependent on the electric field are forbidden for the centrosymmetric cubic crystal structure of garnets and only a square-law on the electric field effect is possible [13].…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Occurrence of linear on the electric field component of EMO signal in some points of a film (Figure 2), in our opinion, has a following explanation. In our earlier studies, only square-law on the electric field EMOE was observed in separate areas of YIG and bismuth-substituted YIG films (without additional external influence on the sample) [8][9][10]. The MEE and EMOE that are linearly dependent on the electric field are forbidden for the centrosymmetric cubic crystal structure of garnets and only a square-law on the electric field effect is possible [13].…”
Section: Resultsmentioning
confidence: 83%
“…After experimentally founding by O'Dell of the magneto-electric effect (MEE) in YIG [7] (MEE-the effect of change of a magnetic state in a solid under the action of an external electric field) the active researches of magneto-electric properties of this ferrimagnetic have begun. In our earlier investigations, MEE in YIG films was studied with using the optical polarimetry method [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In our earlier studies, EMOE was observed in YIG epitaxial films 9, 12, 13. Our experimental techniques as combination of a high‐sensitive laser polarimeter and a polarizing microscope with scanning diaphragm in details described in Ref.…”
Section: Methodsmentioning
confidence: 99%